The influence of brand image and brand personality on brand loyalty, mediating by brand trust : an empirical study - Ahmad Mabkhot, Hashed; Hasnizam Shaari,; Salniza Md. Salleh, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The objective of this study is to investigate the relationships between brand image (BI), brand personality (BP), and brand loyalty (BL) of local automobile brands in Malaysia and determine the mediating effects of brand trust (BT) on the relationships between brand personality (BP) and brand loyalty. This study was carried out because only a few studies have examined the influence of brand image, brand personality, and brand trust on brand loyalty. The Partial Least Squares Structural Equation Modelling (PLS-SEM) was employed in the data analysis. The findings revealed significant relationships between brand image and brand loyalty. However, this study did not find any significant relationships between brand personality and brand loyalty. In addition, brand trust is found to mediate the relationships between brand personality and brand loyalty, and brand trust does not mediate the relationships between brand image and brand loyalty. The study concludes with a discussion on the contributions, limitations as well as suggestions for future research.